(untitled) (Confluenţe Bibliologice, 2017)
Mrs. Margarita Tetelea, PhD Associate Professor, the Head of the Chair, is a brilliant teacher, meticulous researcher and successful manager. She speaks in her interview about her childhood and parents, talent and labour in art, great composers as national heroes, classical music in 21st century and music education at our University (Balti University).